Large-scale SOD1 mutation screening provides evidence for genetic heterogeneity in amyotrophic lateral sclerosis. Issue 5 (3rd December 2009) - van Es, Michael A; Dahlberg, Caroline; Birve, Anna; Veldink, Jan Herman; van den Berg, Leonard H; Andersen, P M
Abstract : Objective: To estimate the frequency of SOD1 mutations in a large referral cohort of familial amyotrophic lateral sclerosis (FALS) and sporadic amyotrophic lateral sclerosis (SALS) patients from The Netherlands and to compare this frequency with that of other developed countries. Methods: A total of 451 sporadic and 55 FALS patients were screened for SOD1 mutations. The authors performed PCR amplification of all five coding exons of SOD1 followed by direct DNA sequencing using forward and reverse primers. Results: One novel mutation (p.I99V) and a homozygous p.D90A mutation were identified in SALS patients. In a pedigree with Mendelian dominant FALS, one patient was found to be heterozygous for the p.D90A mutation. SOD1 mutation frequency was found to be significantly lower in The Netherlands compared with other countries with p=0.0004 for FALS (21.9% vs 2.5%) and p=0.005 for SALS (2.5% vs 0.44%). Conclusions: The authors demonstrate that SOD1 mutations are rare in The Netherlands in familial and SALS. This observation suggests that the genetic background of amyotrophic lateral sclerosis differs between different populations, countries and regions. This may have consequences for the interpretation of association studies and explain why replication of association studies has proven difficult in amyotrophic lateral sclerosis.